KEMAMPUAN MEMAHAMI STRUKTUR ISI TEKS CERPEN SISWA KELAS IX SMP NEGERI 1 WAWOTOBI - Alan, Alan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study is to describe the ability of class IX students of SMP 1 Wawotobi in understanding the structure of text content. This research was conducted in class IX of Wawotobi 1 Public Middle School. The research method used is descriptive quantitative, namely researchers who support compliance in the field that aims to test students' understanding of the structure of the short story text content. The findings in this study are comparisons of students who use the structure of the content of short stories in Indonesian language learning in class IX 1 Wawotobi Junior High School by an Indonesian teacher who discusses through calculating averages (X) Average score of 77, 82 aspects of value assessment the average is 86, 23 and the resolution aspect of the student average score is 82.66. The three aspects are categorized as capable because they are in the range of values ​​of 66-85. Percentage of students' ability to understand the structure of short story texts in learning Indonesian language and literature in class IX of Wawotobi 1 Public Middle School by Indonesian teacher X) is 82.25. This value, if adapted to the quality of the ability to understand the structure of the short story text that has been determined is in the category of capable. Based on this description, it can be concluded that some of the achievements have succeeded in making the structure of the content of the short stories can be mastered by students. The conclusion in this study is the class IX students of Wawotobi 1 Public Middle School depending on the category of being able to improve the structure of the short story text content.